Gender gaps in Australian research publishing, citation and co-authorship - Jamali, Hamid R.; Abbasi, Alireza (Scientometrics, 2023)
Despite improvement in gender inequality in Australian science, the problem has not been fully addressed yet. To better understand the nature of gender inequality in Australian science, all gendered Australian first authored articles published between 2010 and 2020 and indexed in the Dimensions database were analysed. Field of Research (FoR) was used as the subject classification of articles and Field Citation Ratio (FCR) was used for citation comparison. Overall, the ratio of female to male first authored articles increased over the years, and this was true for all FoRs except for information and computing sciences. The ratio of single-authored articles by females was also improved over the study period. Females appeared to have a citation advantage, using Field Citation Ratio, over males in a few FoRs including mathematical sciences, chemical sciences, technology, built environment and design, studies in human society, law and legal studies, and studies in creative arts and writing. The average FCR for female first authored articles was greater than the average FCR for male first authored articles, including in a few fields such mathematical sciences where male authors outperformed females in terms of the number of articles.